Sterilisasi Optimal untuk Kultur Jaringan Bambu Kuning (Bambusa Vulgaris) Secara in Vitro - Miftahul Fikriyah Adudu; Novri Youla Kandowangko; Devi Bunga Pagalla; Jusna Ahmad; Indriati Husain; Lindawaty Isima (Institut Agama Islam Nasional Laa Roiba Bogor, 2025)
Yellow bamboo has great potential in various fields, but its conventional propagation has several obstacles. Tissue culture offers a solution to overcome these problems. The focus of this research is the use of appropriate sterilization for in vitro culture. Effective sterilization is a crucial first step in the success of tissue culture. In this study using sterilization in the form of using Nordox 56 WP, without using Nordox 56WP, using Antracol 5 gr solution, and using HgCl2. The parameters observed were the appearance of contaminants in the form of fungi and bacteria and the time of death of the explants. The results showed that the use of HgCl2 can inhibit contaminants and the time of explant death in yellow bamboo plants in vitro.